PARTISIPASI MASYARAKAT DALAM PEMBANGUNAN KAWASAN EKONOMI KHUSUS MANDALIKA - Lado SS.GP, M.N Zola; Wismayanti, Kadek Wiwin Dwi; Winaya, I Ketut (CITIZEN CHARTER; Vol 4 No 1 (2024): Vol.4 No.1, 2024)
Community Participation In Development Of Mandalika Special Economic Zone (Case Study: Kuta Village, Pujut District, Central Lombok Regency) Development is a continuous government effort with the aim of improving people's welfare. In a development, community participation is one of the important factors that encourage the success of a development. In recent years, the government has sought development by establishing Special Economic Zones in each region that has industrial potential, one of which is the Mandalika Special Economic Zone, Kuta Village, Pujut District, Central Lombok Regency. This research looks at how the participation of the people of Kuta village, Pujut sub-district, Central Lombok district, is in the development of the Mandalika special economic zone. This research uses a descriptive research type with a case study approach. The data sources used are primary and secondary data. The informant fraud technique uses a purposive sampling method. Based on a research study using the participation theory of Cohen and Uphoff (1977), the results of this study indicate that the participation of the people of Kuta Village in the development of the Mandalika Special Economic Zone has been carried out quite well, but there are several problems such as socialization which is still not effective even though several have been implemented. times and the quality of human resources who are still not ready to support the development of the Mandalika Special Economic Zone. In its development, the people of Kuta village actively participate in making development decisions, implementing development, evaluating development and utilizing development results. In making decisions and   evaluating development, the participation of the Kuta village community is carried out by participating in deliberations and meetings, while in the implementation and utilization of development results, the Kuta village community participates by providing the workforce they have. Keywords: Development, Communit Participation, Special Economic Zones